Learning Insularity? Social Capital, Social Learning and Staying at Home among European Youth - Cairns, David (2010)
This paper explores youth mobility in two European regions: Northern Ireland and Portugal. The original research upon which it is based focuses on two specific mobility themes: housing transitions and migration intentions. We have found that almost three quarters of the young people in both samples were living in the parental home, with a significant correlation between living at home and not wanting to migrate in the future. A number of explanations are discussed, including the importance of economic, emotional and social ties in encouraging and inhibiting youth mobility. Our analysis leads us to conclude that many of these young people have learnt to become geographically insular through a social learning process involving strong reliance on the bonding social capital created and embedded in their family relationships.